Bending mode ionic polymer-metal composite (IPMC) pressure sensors. (June 2017) - Gudarzi, Mohammad; Smolinski, Patrick; Wang, Qing-Ming
Highlights: A dynamic IPMC pressure sensor is designed and fabricated using DAP. A signal conditioner is designed to control cutoff frequencies and amplifying gain. Fabricated pressure sensors are calibrated in a pressure tube in several pressures. Proposed IPMC sensors offer an appropriate linearity, sensitivity and reliability. Abstract: Ionic polymer-metal composites (IPMCs) due to their appropriate properties such as flexibility, light weight, easy processing, resilience and high sensitivity have attracted more attentions in recent years. Although there are several studies on basic characteristics of these transducers, developments of IPMC sensors for specific applications are relatively rare. The purpose of this paper is to design dynamic pressure IPMC sensors based on streaming potential hypothesis and calibrate them in a standard shock pressure tube. For this goal, after explaining sensing mechanism based on streaming potential hypothesis for a circular IPMC sensor, direct assembly process (DAP) is applied to fabricate some pressure sensor samples. By estimating equivalent resistance and capacitance of the samples using impedance analyzer, a signal conditioner is designed. A shock tube setup is then utilized for test the performance of the fabricated pressure sensors. Analyzing the results shows that IPMCs as dynamic pressure sensors represent an appropriate linearity, sensitivity and reliability and DAP is a consistent fabrication process for making this category of sensors.